Wage Inequality Within and Between Occupations - Helland, Håvard; Bol, Thijs; Drange, Ida (Nordic Journal of Working Life Studies, 2017)
Western countries, including Scandinavian nations, have witnessed an increase in wage inequality over the past decades. Recent studies attribute rising wage inequality in the United States and United Kingdom primarily to between-occupation inequality, while changes in within-occupation wage inequality were less important for the overall growth. We investigate this hypothesis in the Norwegian context. Our results show a slight increase in inequality from 2003 to 2012, mostly accounted for by between-occupational wage inequality. Occupations became a more important determinant of wages, but the increase in total wage inequality was small. In order to explain trends in wage inequality, we turn to three occupational characteristics: licensure, unionization, and credentialization.